MANAJEMEN PEMBELAJARAN INDIVIDUAL PESERTA DIDIK BERKEBUTUHAN KHUSUS - Sedek, Melky; Nugroho, Piter Joko; Berliani, Teti (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2024)
This research aims to describe the individual learning management of students with special needs at Sekolah Luar Biasa (SLB) Melati Ceria Palangka Raya, which includes aspects of planning, organizing, implementing, and evaluating, as well as supporting factors and constraints. The approach used in this research is qualitative, with data sources consisting of the principal, deputy principal, special mentor teacher, and parents of students. Data were collected through observation, in-depth interviews, and documentation and then analyzed through the stages of data condensation, data presentation, and conclusion drawing. To ensure data validity, triangulation and member check techniques were used. The results showed that the management of individualized learning for students with special needs in SLB Melati Ceria Palangka Raya is well implemented, reflects the practice of special education that is systematic, adaptive, and centered on the individual needs of students, and has a positive impact on increasing the learning motivation of students with special needs.